Personalised Oncology Care: A Case Study on Using an AI-Based App for Chemotherapy Management and Lifestyle Managemen - Gunisetty, Hari Prakash; Doddaiah, Sunil Kumar; Krishnamurthy, Kiran Pura; Arun, Vanishri; Yadav, Deepika; Gopi, Arun (Asian Pacific Journal of Cancer Care, 2025)
This case report explores the use of Mebot, an AI-based mobile application, to enhance medication adherence and lifestyle management in a patient undergoing chemotherapy. Over one week, Mebot was utilised by a patient to manage a complex chemotherapy regimen, providing timely reminders for medication intake and generating personalised exercise plans to support weight reduction. The app’s “connected dots” functionality allowed for integrating related tasks like medication and exercise into a seamless health management approach. Multiple users, including the authors of this report, tested the app and reported consistent, satisfactory results, highlighting Mebot’s reliability and effectiveness. The study findings suggest that Mebot could be a valuable tool in managing non-communicable diseases (NCDs) by improving adherence to treatment protocols and supporting lifestyle interventions. However, further research involving more prominent and diverse populations is necessary to validate these preliminary observations and explore the broader applicability of AI-driven mobile applications in personalised oncology care.